Is there a Place for Tonsillar Punch Biopsy in the Diagnosis of Chronic Tonsillitis? - Ahmet Kutluhan; Faruk Kıroğlu; Muzaffer Kırış; Serdar Uğraş; Nusret Akpolat; Hayrettin Akdeniz (Turkish Archives of Otorhinolaryngology, 2001)

(untitled)
We investigated if there is a place of tonsillar punch biopsy in the diagnosis of chronic tonsillitis. This prospective study was held on 100 patients whom we were able to get reliable anamnesis and underwent tonsillectomy because of chronic tonsillitis. Control group consisted of 20 voluntary persons who do not have pharyngeal symptoms but have been operated due to another reason in our clinic. Histopathological criteria of chronic tonsillitis were examined on tonsillectomy materials of patients group, punch biopsy specimens obtained from them, and punch biopsy specimens of control group. In tonsillectomy materials, severe lymphocyte infiltration to surface epithelium and surface epithelial defect were determined respectively in rates of 96% and 88%, whereas these rates in punch biopsies of the same tonsils were found respectively as 89% and 75%. In tonsil punch biopsy specimens of control group severe lymphocyte infiltration to surface epithelium and surface epithelial defect were noted respectively as 15% and 3%. According to Kappa test, the rates of histopathological criteria of chronic tonsillitis in patient group showed good correlation between tonsillectomy materials and their punch biopsy specimens. This result reveals that tonsil punch biopsy which is an easy and reliable method may be used in suspected cases in diagnosis of chronic tonsillitis.